2023
DOI: 10.1126/sciimmunol.adg3196
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of GSDMB modulates killer lymphocyte–triggered pyroptosis

Abstract: Granzyme A from killer lymphocytes cleaves gasdermin B (GSDMB) and triggers pyroptosis in targeted human tumor cells, eliciting antitumor immunity. However, GSDMB has a controversial role in pyroptosis and has been linked to both anti- and protumor functions. Here, we found that GSDMB splicing variants are functionally distinct. Cleaved N-terminal (NT) fragments of GSDMB isoforms 3 and 4 caused pyroptosis, but isoforms 1, 2, and 5 did not. The nonfunctional isoforms have a deleted or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“… 163 However, two other studies point out that GSDMB3, like GSDMB4, also has pro-pyroptosis activity, as GSDMB3 also has a stable band motif encoded by exon 6. 37 , 164 These research discrepancies warrant further investigation. However, these findings hold significant value in elucidating the intricate roles of GSDMB isoforms in disease pathogenesis and in informing the future design of targeted GSDMB therapies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“… 163 However, two other studies point out that GSDMB3, like GSDMB4, also has pro-pyroptosis activity, as GSDMB3 also has a stable band motif encoded by exon 6. 37 , 164 These research discrepancies warrant further investigation. However, these findings hold significant value in elucidating the intricate roles of GSDMB isoforms in disease pathogenesis and in informing the future design of targeted GSDMB therapies.…”
Section: Introductionmentioning
confidence: 94%
“…It is worth pointing out that the cleavage products of GSDMs do not always result in cell death. Specifically, NT domains of GSDMB isoforms 3 and 4 are able to cause pyroptosis, whereas isoforms 1, 2, and 5 are not, 37 suggesting that cells may inhibit and evade pyroptosis by generating noncytotoxic isoforms of GSDMB. Ongoing studies of the GSDM family have delved into the mechanisms of PCD and inflammation, highlighting the necessity for comprehensive inquiries into the roles and operational mechanisms of these molecules in both health and disease states.…”
Section: Introductionmentioning
confidence: 99%
“…While classically thought to be non-cytotoxic, IL-15 increases expression of granzyme (Gzm)A, B and C and may promote ILC1s towards a cytotoxic phenotype against tumours [ 78 82 ]. Mechanistically, GzmA causes lytic granule-mediated noncanonical apoptosis and pyroptosis [ 83 , 84 ]. Intriguingly, comparison of chromophobe renal cell carcinoma (RCC; chRCC) to clear cell RCC (ccRCC) in human patients revealed that chRCC tumours express higher levels of IL-15, and this is reflected by the higher expression of GzmA in ILC1s compared to NK cells in chRCC, while the opposite is observed in ccRCC which express minimal levels of IL-15 [ 78 ].…”
Section: Il-15-granzyme-ilc1 Axismentioning
confidence: 99%
“…Nevertheless, GSDMB has a controversial role in pyroptosis. Kong et al reported that GSDMB splicing variants present functional distinction: Cleaved N‐GSDMB isoforms 3/4 can cause pyroptotic cell death, but isoforms 1/2/5 cannot 40 . Streptococcal pyrogenic exotoxin B enables to cleave GSDMA and evoke pyroptosis 41 .…”
Section: Overview Of Stress/cell Death Pathwaysmentioning
confidence: 99%